Clinical Utility of C-Reactive Protein and White Blood Cell Count for Scheduling an [18F]FDG PET/CT in Patients with Giant Cell Arteritis - Guggenberger, Konstanze V.; Vogt, Marius L.; Rowe, Steven P.; Higuchi, Takahiro; Schmalzing, Marc; Tony, Hans-Peter; Buck, Andreas K.; Bley, Thorsten A.; Fröhlich, Matthias; Werner, Rudolf A. (Nuklearmedizin - NuclearMedicine, 2022)
Objectives 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) PET/CT can be utilized in patients with giant cell arteritis (GCA), but pretest probability of established laboratory marker such as C-reactive protein (CRP) and white blood cell count (WBC) has not been defined yet. We aimed to elucidate the clinical utility of CRP and WBC for scheduling an [18F]FDG scan.Methods 18 treatment-naïve GCA patients and 14 GCA subjects with anti-inflammatory treatment (glucocorticoids or comparable drugs), who underwent [18F]FDG PET/CT and who had no other inflammatory disease at time of scan, were identified. A semi-quantitative analysis in 11 vessel segments was conducted, with averaged jugular vein, healthy liver and lung tissue (Target-to-background ratio [TBR]VJ/liver/lung) serving as background. Derived TBR were then correlated with CRP and WBC at time of PET using Spearman’s correlation.Results For all treatment-naïve patients, TBRVJ was 2.3±1.1 (95%CI, 2.2–2.5), TBRliver was 1.0±0.5 (95%CI, 0.9–1.0) and average TBRlung was 6.3±3.6 (95%CI, 5.8–6.8). No significant correlation was noted for either CRP (TBRVJ: R=–0.19; TBRliver: R=–0.03; TBRlung: R=–0.17; each P ≥ 0.44) or for WBC (TBRVJ: R=–0.40; TBRliver: R=–0.32; TBRlung: R=–0.37; each P ≥ 0.10). Similar results were recorded for patients under treatment at time of PET. Again, no significant correlation was reached for either CRP (TBRVJ: R=–0.17; TBRliver: R=–0.28; TBRlung: R=–0.09; each P ≥ 0.32) or WBC (TBRVJ: R=–0.06; TBRliver: R=–0.13; TBRlung: R=0.06; each P ≥ 0.65).Conclusions In GCA patients with and without anti-inflammatory treatment, CRP and WBC did not substantially correlate with TBR at time of scan. Given the rather limited pretest probability of those parameters, such laboratory values may have less diagnostic utility to order an [18F]FDG PET/CT.
Keywords: Großgefäßvaskulitis; Riesenzellarteriitis; [18F]FDG PET/CT; C-reaktives Protein; Weiße Blutkörperchen